Decorated Wooden Ceilings of the Burji Mamluk Period in Cairo - El Azzouni, Zein (AUC Knowledge Fountain, 2025)
The decorated wooden ceilings still located in their original surroundings within Cairene-Burji sites form the starting point of this work. A survey of these artifacts in their intended location provides a useful opportunity to reflect on their lived context, and to study the reciprocity between forms and designs across various artifacts in the same site, woodworked or otherwise. All aspects of the structure and decoration of these ceilings are examined in the present study. A provisional typology will first be presented for ceilings from the late-Ayyubid period up to the Burji-Ottoman cusp. In view of the similarities between late-Ayyubid and Bahri ceilings with those found later in the Burji period, it seems pertinent to include them for consideration. Various connections are explored with relevant traditions outside of Cairo and Egypt, in particular those from Bilad al-Sham, Yemen, Iberia and North Africa, in order to arrive at an understanding of the wider context, possible origins, and significance of these styles. The focus then moves to a consideration of the concurrent development of cornices and spandrels, linked intrinsically to the ceilings which surmount them, then to a review of materials and techniques, and after that to an analysis of ornamentation and epigraphy. Finally, a brief inquiry into the development and forms of lantern ceilings, of which none survive intact from the Burji period, will be conducted.